PENINGKATAN SERVIS BAWAH BOLA VOLI MENGGUNAKAN PENDEKATAN BERMAIN DI SDN 04 SUNGAI AYAK - Yusmaniar, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to determine Improved service learning approach play volleyball in class V students of State Elementary School 04 Sungai Ayak Sekadau. Forms of research is classroom action research. Subjects in this study were fifth grade students of State Elementary School 04 Sungai Ayak Sekadau. The total number of male students in class V are as many as 21 students. Based on the results of research on service learning outcome down to play volleyball with the approach of the first cycle are the result of the thoroughness with the number of 13 students or 68%, and students who have not completed amounted to 8 students or by 32%. While the second cycle there is a category of student outcomes to complete all of the graduating students are 25 students or equal to 100 % and unresolved amounted to 0 or does not exist. Keywords: Service Down, Playing approach